Utilization of cellulose microfiber from pineapple leaf as lipase immobilization support for highly retained activity, ease of separation and reusability - Thitinun Pradubsang (2019)
© 2018 Science Society of Thailand under Royal Patronage. All rights reserved.. We investigate the use of cellulose microfibre from pineapple leaf, referred to as pineapple leaf microfibre (PALMF), as a support for the immobilization of lipase AY from Candida rugosa. PALMF was produced from pineapple leaf waste with a very fine diameter of about 3 μm. It disperses very well in aqueous media and can easily be filtered out. PALMF in the forms of loose fibre and of mat were used. Different amounts of enzyme were immobilized on these PALMFs and tested for their hydrolytic activity. The reusability of the immobilized enzyme was also studied. The results showed that, for the selected amount of lipase used, enzyme loading and PALMF form affect the hydrolytic activity of the enzyme. Immobilized enzymes display slightly lower hydrolytic activity than the free enzyme. The activity decreases when the enzyme loading (on PALMF) is increased. Lipase AY immobilized with optimum quantity (1.37 mg/g of PALMF support) displayed a 12% drop in activity from that of free enzyme. The crowding of enzyme molecules on the PALMF surface caused steric hindrance and reduced accessibility to the active site of the enzyme. So with the suitable amount of immobilized enzyme on PALMF, reasonable hydrolytic activity together with easy separation and reusability can be obtained. This method could aid significantly the use of enzyme in industrial processes.